1967
DOI: 10.1113/jphysiol.1967.sp008230
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic response of brain slices to agents affecting the sodium pump

Abstract: SUMMARY1. Slices of brain cortex from rabbits were incubated in Ringer solution and in Ringer modified by the removal of calcium and sodium, and the addition of ouabain, oligomycin or extra potassium. The potassium content of the tissue, the oxygen consumption and the lactate production from glucose were measured and found to be interrelated.2. Incubation in high-K Ringer caused an increase in oxygen consumption that was prevented by ouabain, oligomycin and deprivation of sodium. Lactate production was also ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…As in previous experiments in vivo 12 , inhibiting the sodium–potassium pump approximately halved the total energy expenditure in our brain slices. However, as in cortical slices, 58 , 59 this pronounced reduction in oxygen consumption was seen only when external calcium was absent, and the decrease in oxygen consumption was inhibited when calcium was present in the external solution ( Figure 6 ). It is known that, with extracellular calcium present, blocking the sodium pump with ouabain induces a rise of intracellular [Ca 2+ ] i , due to Na + gradient rundown and subsequent reversal of the Na + /Ca 2+ exchanger 60 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…As in previous experiments in vivo 12 , inhibiting the sodium–potassium pump approximately halved the total energy expenditure in our brain slices. However, as in cortical slices, 58 , 59 this pronounced reduction in oxygen consumption was seen only when external calcium was absent, and the decrease in oxygen consumption was inhibited when calcium was present in the external solution ( Figure 6 ). It is known that, with extracellular calcium present, blocking the sodium pump with ouabain induces a rise of intracellular [Ca 2+ ] i , due to Na + gradient rundown and subsequent reversal of the Na + /Ca 2+ exchanger 60 .…”
Section: Discussionmentioning
confidence: 77%
“…These experiments were performed both in the presence and absence of external calcium, because blocking the pump is expected to lead indirectly to a rise of [Ca 2+ ] i which can increase energy consumption (see Discussion). For example, while Shibuki 58 found that ouabain decreased oxygen consumption in unstimulated neurohypophysis slices whether or not calcium was present, Ruščák and Whittam 59 found that blocking the Na + /K + pump only decreased O 2 consumption in cortical slices when using Ca 2+ -free external solutions, and instead found an increase in O 2 consumption when the external solution contained Ca 2+ . Because of these varying results, we measured the effect of blocking the sodium pump on the [O 2 ] profile both in the presence and absence of external calcium.…”
Section: Resultsmentioning
confidence: 99%